Observation on a collection of Tawny Coster Acraea terpsicore (Pieridae: Lepidoptera) in the web of the Social Spider Stegodyphus sarasinorum (Eresidae: Araneae) - Patel, Niyati S. (Journal of the Bombay Natural History Society (JBNHS), 2013)
No Abstract.